2009
DOI: 10.1063/1.3247903
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a fast Fourier transform-based nonlinear dielectric spectrometer

Abstract: Nonlinear dielectric spectroscopy of micro-organism is carried out by applying a moderate electrical field to an aqueous sample through two metal electrodes. Several ad hoc nonlinear spectrometers were proposed in the literature. However, these designs barely compensated the nonlinear distortion derived from the electrode-electrolyte interfaces (EEI). Moreover, the contribution of the suspension is masked by the effect of the nonlinearity introduced by the electrode contacts. Conversely, the nonlinear capabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…To administer a sinusoidal voltage with a low frequency and a high amplitude, we utilized the Instek-AFG. The harmonics of the device across the whole range of amplitudes fall below −60 dBc, making it appropriate for NLDS. , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To administer a sinusoidal voltage with a low frequency and a high amplitude, we utilized the Instek-AFG. The harmonics of the device across the whole range of amplitudes fall below −60 dBc, making it appropriate for NLDS. , …”
Section: Methodsmentioning
confidence: 99%
“…Initially, we used a circuit phantom, specifically that presented by Treo and Felice, 13 to assess the accuracy of our method. We utilized this phantom to measure the current harmonic generated by it and subsequently compared the obtained data with the simulation conducted in Spice.…”
Section: Experimental Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, low voltage, lower frequency (~100 Hz) sinusoidal excitation has been found to generate harmonics in whole cells, but the origin of the harmonics and the connection with membrane protein activity has not been well-elucidated [ 7 , 14 , 15 , 16 ]. We have previously reported that 4-probe nonlinear dielectric spectroscopy is sensitive to the metabolic state of budding yeast [ 7 ], but this previous work did not explore if the harmonics originated from the bulk of the suspension [ 17 ] or from the electrode interfacial region [ 16 ]. This information is important for understanding the relationship between metabolism and the applied electric field.…”
Section: Introductionmentioning
confidence: 99%